If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 12 = -2x + -8 Reorder the terms: 12 + 2x = -2x + -8 Reorder the terms: 12 + 2x = -8 + -2x Solving 12 + 2x = -8 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 12 + 2x + 2x = -8 + -2x + 2x Combine like terms: 2x + 2x = 4x 12 + 4x = -8 + -2x + 2x Combine like terms: -2x + 2x = 0 12 + 4x = -8 + 0 12 + 4x = -8 Add '-12' to each side of the equation. 12 + -12 + 4x = -8 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = -8 + -12 4x = -8 + -12 Combine like terms: -8 + -12 = -20 4x = -20 Divide each side by '4'. x = -5 Simplifying x = -5
| .8(1+.5x)=.1(12+x) | | (7c+5)(3c-6)=0 | | 2(4x+2)=6x+2x+4 | | 6x+26=10x+18 | | -9(b^2+2b-3)+b(2b+5)+7= | | x^2-129x=0 | | 190+0.15x=322 | | -6(g+4)=12 | | -(8y+2)-(-7y-8)=-1 | | 4x+16=26 | | Y=(6x+3)(5x+4) | | x+11=11-5x | | 7w-4w-8=7 | | h+(-3)+9=-1+14 | | -6x^2+5x-2=0 | | 10a=3a+9+6a | | Y-16=11(x-1) | | b^4-5b^2-6b=0 | | .77=(1/x) | | x^4+9x^2+4=0 | | .77=1/x | | x/24-1.4=8.3 | | (X+4)-x-(5-6x)=11 | | Y=(6x+3)10 | | 8x+6y=-26 | | 2a+4(2-a)-6(1+a)=18 | | m+(-6)=22 | | 15+4ln(x)=10 | | Z-19=19 | | 2(x+6)=-2x(x-4) | | 5.25=1.25 | | 5[x+9]=80 |